Filler Use in EFL Speaking: A Cognitive and Communicative Analysis of English Club Interactions - Ukiarti, Pursa Cahya; Fitriati, Sri Wuli (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
Fillers are commonly regarded as indicators of speech disfluency in English as a Foreign Language (EFL) communication; however, their strategic role in natural extracurricular speaking environments remains underexplored, particularly in cognitively demanding interactions such as debates. This study aims to investigate the types of fillers produced by EFL learners, examine their communicative functions, and explore students’ perceptions of filler use during English Club activities. A descriptive qualitative design was employed involving 15 English Club members at a senior high school in Pekalongan, Indonesia. Data were collected through audio recordings, classroom observations, and semi-structured interviews, and analyzed using qualitative content analysis. The findings revealed that students predominantly employed short lexical and unlexicalized fillers to maintain speech continuity, gain planning time, organize ideas, and manage real-time interaction, especially during debate sessions requiring higher cognitive processing. Interview data further indicated that students perceived fillers as useful strategies for sustaining fluency and reducing communication anxiety, although excessive use was considered detrimental to clarity and speaker credibility. This study contributes to the understanding of fillers as strategic components of communicative competence rather than mere signs of disfluency and highlights the pedagogical importance of fostering balanced filler use to support spontaneous speaking performance in EFL contexts.